E-Module Implementation by Using Feature-Lesson-Based of Moodle in Physics Learning Multimedia Practices for Students of Prospective Physics Teacher (Jurnal Pendidikan Fisika Indonesia, 2023)
The rapid development of Information and Communication Technology (ICT) allows tertiary institutions to hold lectures offline, blended, and online. Nonetheless, findings in the field show that online lectures cannot guarantee whether students follow lecture material properly or not. Therefore, this study aimed to implement an e-module of the feature-lesson-based developed by Moodle for physics learning multimedia practice course. This e-module was developed using the ADDIE model which includes analysis, design, development, implementation, and evaluation stages. The developed e-module in this study used the feature-lesson to ensure students follow the material properly and coherently. Students can access the next material if they have mastered the material that has been presented. The data in this study were collected through the responses of prospective physics teacher students who had used the e-module for one semester. Student responses included the use of the feature-lesson to support coherent mastery of the material, the application of the feature-lesson in presenting the learning process through e-modules, the use of quizzes on the feature-lesson to ensure achievement of learning outcomes, and the interest of prospective teacher students in developing online learning using the feature-lesson on Moodle. The results of student responses showed that the e-module implementation of the feature-lesson-based of Moodle in physics learning multimedia practice were in very good criteria. Students liked the feature-lesson because they should follow the order in which the material was given so that it helped them understand the material properly and coherently. In addition, students can understand the material better because when they choosed the wrong answer in a quiz, students would be directed to review material that they have not understood. Students can continue to the next material if they have been able to complete the quiz correctly